Análise da estabilidade estrutural de telhas autoportantes fabricadas por conformação a frio de chapas finais de aço - Garcia, João Pedro Magalhães (2018)
The present research is addressed to the study of stiffened cold-formed steel sheeting aiming at improving steel roofing system with the help of two semiautomatic procedures sequences. The first one (A) adopts elastic stability analysis and the related critical flexural bending moments, while the second (B) is referred to a resistance curve proposed by the author based on Finite Elements model analysis. The results of study A indicate that (i) minor modifications of the cross-section geometry may affect the local (L) and distortional (D) buckling modes; (ii) several solutions include very close critical buckling moments which may conduct to possible buckling modes interaction and (iii) the shape of these sections exceeds the limits proposed by AISI for the calculation by the Direct Resistance Method. Conversely, the results of study "B" indicate that (i) the flexural strength of these profiled sheeting is less sensitive to the variation of most of the proposed geometric parameters, (ii) the proposed resistance curve captures the interaction L-D and (iii) the proposed strength curve is shown valid only for a narrow domain of geometric parameters. Additionally, it has been observed that D mode tends to become dominant for resistance calculation. The bibliographic review confirms the validity limitations of the modal classification criteria and points to future developments of this work.